2009
DOI: 10.1371/journal.pntd.0000365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Behavioral Differentiation among Brazilian Populations of Lutzomyia longipalpis (Diptera: Psychodidae: Phlebotominae)

Abstract: Background Lutzomyia longipalpis is the primary vector of American visceral leishmaniasis. There is strong evidence that L. longipalpis is a species complex, but until recently the existence of sibling species among Brazilian populations was considered a controversial issue. In addition, there is still no consensus regarding the number of species occurring in this complex.Methodology/Principal FindingsUsing period, a gene that controls circadian rhythms and affects interpulse interval periodicity of the male c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
138
2
21

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(173 citation statements)
references
References 64 publications
8
138
2
21
Order By: Relevance
“…Other variations in populations of L. longipalpis from Central and South America have been reported, such as behavioral, morphological and biochemical characteristics (Dias et al 1998, Lampo et al 1999, Araki et al 2009, and the existence of reproductive isolation among populations from Central and South America mediated by different sex pheromones has been already suggested (Ward et al 1988).…”
Section: Introduc Onmentioning
confidence: 91%
See 2 more Smart Citations
“…Other variations in populations of L. longipalpis from Central and South America have been reported, such as behavioral, morphological and biochemical characteristics (Dias et al 1998, Lampo et al 1999, Araki et al 2009, and the existence of reproductive isolation among populations from Central and South America mediated by different sex pheromones has been already suggested (Ward et al 1988).…”
Section: Introduc Onmentioning
confidence: 91%
“…Studies supporting the hypothesis of the existence of a complex of species have been conducted using different methods to evaluate different populations of L. longipalpis, such as analysis of hybridization (Ward et al 1983), sex pheromones (Ward et al 1988, Hamilton et al 1996, isoenzyme pro ile analysis (Lanzaro et al 1993, Arrivillaga et al 2000, cytogenetic characters (Yin et al 1999), male copulation songs (Sousa et al 2002, Araki et al 2009, analysis of mitochondrial DNA (Arrivillaga et al 2003) and microsatellite markers (Maingon et al 2003, Watts et al 2005.…”
Section: Introduc Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutzomyia longipalpis is found from southern Mexico (20°N) to Argentina (27°S), with several indications that this sandfl y might encompass a species complex 6 Mark-release-recapture experiments in urban areas of the same city 9 have shown that the maximal dispersion distance for adult sandfl ies is 243m. However, the same type of experiments conducted in the rural communities of Marajó, Pará showed a maximal dispersion distance of 700m 10 .…”
mentioning
confidence: 99%
“…longipalpis populations was published after the meeting by Araki et al (2009). These authors performed a combined analysis of different characters (molecular polymorphism of selected genes, copulation song patterns and pheromone types) and confirmed the occurrence of sympatric sibling species in new localities.…”
Section: A Group Of 18 Research Workers Involved In Different Aspectsmentioning
confidence: 88%